Air core notch-coil magnet with variable geometry for fast-field-cycling NMR - Kruber, Stephan; Farrher, Germán David; Anoardo, Esteban (2022)
Fil: Kruber, Stephan. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.